Zion Christian Church, Masvingo - Heijke, Jan P. (Mission Studies, 1985)
Part of III. Exposure Experiences in Zimbabwe and South Africa
paid
Keywords: African independent churches; Mutendi; Nehemiah; Bp; Zimbabwe – Church history; Zion Christian Church